2017
DOI: 10.1111/apa.13710
|View full text |Cite
|
Sign up to set email alerts
|

A rectally administered combination of midazolam and ketamine was easy, effective and feasible for procedural pain in children with cerebral palsy

Abstract: Rectally administered midazolam and racemic ketamine provided effective pain relief for paediatric cerebral palsy outpatients receiving painful injections and was a viable alternative to inhalation analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 27 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…Management of procedural pain was evaluated for ( n =number of studies): intramuscular BoNT‐A injections ( n =5), acupuncture ( n =1), and venepuncture ( n =1) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of procedural pain was evaluated for ( n =number of studies): intramuscular BoNT‐A injections ( n =5), acupuncture ( n =1), and venepuncture ( n =1) …”
Section: Resultsmentioning
confidence: 99%
“…Pain during BoNT‐A injections was managed with: inhaled nitrous oxide with topical anaesthetic cream ( n =2); ketamine with midazolam ( n =2); and clown‐care therapy ( n =1) . Observational studies reported mixed evidence for the efficacy of inhaled nitrous oxide with topical anaesthetic cream.…”
Section: Resultsmentioning
confidence: 99%
“…insertion has to be considered by clinicians for children. As alternative routes, a small number of studies evaluated rectal, 40 , 41 intranasal 42 45 and submucosal 46 administration in the paediatric setting ( Table 1 ). The rectal ketamine route was suggested in a clinical trial by Nilsson et al performing sedation and analgesia in 61 children with cerebral palsy).…”
Section: Reviewmentioning
confidence: 99%
“…Botulinum toxin treatment has most often been used in 4–6-year olds to reduce spasticity (Franzen, Hägglund & Alriksson-Schmidt 2017). Healthcare professionals should offer evidence-based intervention, such as BoNT, although it is necessary to carry out intervention in a comfortable way (Nilsson et al 2017).…”
Section: Additional Resources Perceived As Missingmentioning
confidence: 99%